Challenging homophobia in schools: policies and programs for safe school climates - Russell, Stephen T. (Educar em Revista, 2011)
<!--[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--><!--[if gte mso 10]> <![endif]--> In the United States there has been growing public and scientific attention to homophobia in schools. A well-established body of research documents persistent and pervasive bullying, harassment and lack of safety at schools towards lesbian, gay, bisexual, and transgender (LGBT) students. This work makes clear that contemporary school and youth cultures are characterized by rigid gender and sexuality norms (including homophobia and expectations regarding masculinity, femininity, and heterosexuality); the well-being of students who do not conform to or who challenge these norms is often undermined. In recent years there has been a shift from consideration of the plight of individual students to the acknowledgement that the school context or climate must be better understood in order to prevent bias-motivated bullying and promote school safety and student well-being. During the last decade a number of studies have identified specific education policies, programs, and practices that promote safe school climates. In this article I review what is known about policies and programs that promote safety for LGBT as well as heterosexual students in schools. A growing body of work indicates that the following strategies are associated with safer school climates for LGBT students: enumerated school nondiscrimination and anti-bullying policies; teacher intervention when harassment takes place; availability of information and support about LGBT concerns for students; the presence of school-based support groups or clubs (often called “gay-straight alliances”); and curricular inclusion of LGBT people and issues. In the context of this research, I discuss several key issues for consideration by educators, policy-makers, and scholars. Keywords: school climate; homophobia; bullying.